The Existence of Fleas in Rodents at Plague Observation Area in Nongkojajar Pasuruan Regency - Sugeng Riyanto (Universitas Airlangga, 2019)
The existence of rodents and vectors are still a critical threat for human life and public health due to its potentials in transmitting diseases. Rodents, especially rats are the main source of plague transmission, leptospirosis, rickettsiosis, and nematode worms are also a fleas host as a carriers vector of bacteria cause plague and rickettsiosis. This study aimed to identify the number and types of rats and fleas in the plague observation area in Nongkojajar Sub District, Pasuruan Regency. This research was an observational study with time series design. The researcher used secondary data from Environmental Health Technology and Development Bureau (BBTKLPP) Surabaya in Epidemiology Surveillance Division. The population was all rats and fleas caught in during 2014-2018. This study was held on October 2018 in Surabaya. The data was presented in the form of tables and graphs. Rats caught from 2014-2018 were mostly indoor rats in the house. Results of rats sweeping found two types of main fleas in majority, the number of Xenopsylla cheopis was higher than Stivalius cognatus. Analysis data at week 4-26 in 2018 found the most of rats caught were the types of Rattus rattus diardii, Rattus exulans, Suncus murinus, Hilomis suilus, and other types of rats. Most caught type of rats in the area of PES observation in Nongkojajar Pasuruan was Rr. diardi in the house. Most type of fleas found is Xenopsylla cheopis. The conclusion of this study: It is recommended to strengthen vector control and monitoring program in Nongojajar order to avert the elevated incidence cases of plague, leptospirosis, rickettsia and nematoda.